PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE PENCARIAN PENILAIAN TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 10 PALEMBANG - Ima Siti Maryam; Yulia Djahir; Fitriyanti Fitriyanti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The problem in this research is whether there is difference of influence of active learning strategy of type search of appraisal with active learning strategy type learn from fellow to student learning result on economic subject at SMA Negeri 10 Palembang ?. The purpose of this research is to know the difference of influence of active learning strategy of type search of appraisal with active learning strategy type learn from fellow to learner result of student in Economic subject at SMA Negeri 10 Palembang. The research is a type of True Experimental Design. Population in this study all students of class X in SMA Negeri 10 Palembang consisting of eleven class which amounted to 416 learners. The sampling technique was taken using Cluster Random Sampling, so selected class X.2 as experiment class and class X.4 as control class. Data collection techniques used tests and observations. The statistic used to test the hypothesis using t-test with significant level (α = 0,05) or 5% and dk = n1 + n2 - 2. Based on data analysis through t-test obtained t count> ttable that t count equal to 34, 90> t table of 1.995. Thus the hypothesis proposed in this study can be accepted truth that there are differences in the influence of active learning strategy type of assessment search with active learning strategy of learning type of fellow to learners' learning outcomes on subjects Economics in state Senior High School 10 Palembang.